Analisis Buku Ajar Bahasa Arab Karya Dr. D. Hidayat - Mabrurrosi, Mabrurrosi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
Books are an integral part of teaching and learning activities. So far, textbooks have become the most widely used media in transferring knowledge and knowledge to students. However, the ability to compile books properly and according to the mandate of the curriculum cannot be done by everyone. Therefore, it requires exposure and content analysis in textbooks. In this research, the learning content contained in the Arabic language book by Dr. D. Hidayat for grade 6 MI. This study aims to describe the content of teaching materials and identify them according to the principles of teaching material analysis so that teachers can see the strengths and weaknesses of the book.